Clinical characteristics and humoral immune response in healthcare workers with COVID-19 in a teaching hospital in Belgium. Issue 4 (December 2020) - Vandercam, G.; Simon, A.; Scohy, A.; Belkhir, L.; Kabamba, B.; Rodriguez-Villalobos, H.; Yombi, J.C.
Summary: Background: Healthcare workers (HCWs) are at high risk of acquiring COVID-19 and could play a role in nosocomial transmission. Since 4 th February 2020, Belgian Health authorities reported more than 90, 568 cases, of which 8.3% were HCWs. Data on clinical characteristics, sources of infection and humoral immune response of HCWs with COVID-19 remain scarce. Aim: To analyse the clinical characteristics, humoral immune response, sources of contamination, and outcomes among HCWs with COVID-19. Methods: This retrospective study included 176 HCWs with laboratory-confirmed COVID-19 in a teaching hospital in Belgium. Between 1 st March and 31 st May 2020, all HCWs with symptoms suspected of COVID-19 were tested by reverse transcription polymerase chain reaction on a nasopharyngeal swab. Serological testing was performed between 55 and 137 days after the onset of symptoms. Findings: Median age was 40.8 years and 75% were female. Median delay between onset of symptoms and diagnosis was 4.39 days. Most frequent symptoms were cough and headache (both 75%). Fever accounted for 68.7%. Most represented professions were nurses (42%). HCWs were mainly infected by patient contact (32.9%); 7.6% required hospitalization and 1.7% were admitted to the intensive care unit. Unfortunately, one HCW died (0.5%). Total antibodies were positive in 109/126 (86.5%). Conclusions: Clinical presentation of COVID-19 in HCWs does not differ from the general population. However, outcomes were more favourable with a mortality rate lower than that reported in Belgian COVID-19 patients in general (16%). The main source of infection was the hospital setting. Our positive antibodies rate was high but lower than previously reported.